Partial Social Integration as a Predictor of COVID-19 Vaccine Rejection and Distress Indicators - Yohanan Eshel; Shaul Kimhi; Hadas Marciano; Hadas Marciano; Bruria Adini (Frontiers Media S.A., 2022)
Partial social integration refers to the perceived exclusion of individuals or groups, from full participation in their society. The current study claims that perceived partial social integration (PPSI) constitutes a substantial predictor of the rejection of the COVID-19 vaccine, a significant mediator of the impact of demographic variables (such as age and level of income) on this vaccine rejection, and an important predictor of indices of psychological distress during pandemic times. Previous publications show that although vaccines constitute a very efficient means for countering pandemics, vaccine hesitancy is a prevalent public response to the COVID-19 pandemic. The present study is one of a few studies examining the impact of psychological variables on the actual behavior of vaccine rejection rather than on the cognitive element of vaccine hesitancy. A sample of 600 Israeli Jewish adults responded in February 2022 to an anonymous questionnaire exploring, among other issues, the (PPSI), the individual level of vaccine uptake, and the level of distress of these individuals. Path analyses of the variables predicted by PPSI indicated the following results: (a) PPSI score negatively predicted vaccine uptake level and significantly mediated the effects of age and family income on the level of vaccination. (b) PPSI levels significantly predicted higher levels of anxiety, depression, and a sense of danger and negatively predicted societal resilience. The discussion elaborates the contention that the PPSI is a substantial cause of psychological distress and in compliance with the pandemic vaccination guidelines, despite the potential health risk involved.